Snapshot of Non-Inclusive Growth: Evidence from Philippine Employment Trends in 2001-2009 - Mendoza, Ronald U (Archīum Ateneo, 2012)
This article briefly examines the Philippines’ pattern of job creation during the period 2001-2009 in order to help explain why growth during this period failed to translate into poverty reduction. An analysis of disaggregated employment and sectoral output data provides a much more nuanced picture of the types and sectors of jobs created during the last decade. The empirical evidence suggests that employment creation was inadequate, and skewed in favor of high skilled workers even across industries. Based on these findings, promoting inclusive growth in the Philippines requires a robust job creation strategy in order to meet the growing labor force, along with mechanisms to ensure skill upgrading and better skills matching (notably for the young) as well as efforts to bring even lower skilled workers into the formal sector.